Implementation of the Green Library as an Effort to Strengthen Library Support for UI GreenMetric - Haryanto, Haryanto; Dewi, Nita Triana; Sukma, Dara Pustika (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
The Green Library has emerged as a key strategy in promoting environmental sustainability within higher education institutions. This study explores the implementation and impact of Green Library practices at the Library of Universitas Sebelas Maret (UNS) and their contribution to the university’s performance in the UI GreenMetric ranking. A qualitative descriptive approach was employed, with data collected through observation, document analysis, and informal interviews involving four groups of informants: librarians, faculty members, students, and representatives from the Sub-directorate of Green Campus and SDGs at UNS. The library’s sustainability initiatives include paperless digital services, waste segregation, energy-efficient lighting, and user-centered environmental education. Informants acknowledged the library’s positive role but also pointed out existing gaps, such as the absence of a formal roadmap and a systematic reporting mechanism. This study affirms the library’s strategic role in driving sustainable campus transformation and recommends enhancing institutional collaboration, adopting data-driven reporting, and developing long-term sustainability policies.